Comparison study of corrosion measurement technique - Fadli, Mislan@Mishadi (2013)
Corrosion monitoring tests were carried out to compare some of electrochemical techniques and non-electrochemical technique to measuring the corrosion rate and to study the uncertainty of the these techniques. Each of technique have their errors from the experimental method and equation of the theory. In atmospheric condition, 3.5% wt of NaCl will be used as solution for electrochemical techniques,while for weight loss will immersed in that solution at certain time of period. The data from electrochemical method were analyzed by using Ivman software and to be compare the result of each technique. The experiment were carried out at atmospheric condition and at room temperature.